The importance of the lifelike esthetic appearance of all-ceramic restorations on anterior teeth - Santos, Daniela Micheline dos [UNESP]; Moreno, Amália [UNESP]; Vechiato-Filho, Aljomar José [UNESP]; Bonatto, Liliane da Rocha [UNESP]; Pesqueira, Aldiéris Alves [UNESP]; Laurindo Júnior, Murilo César Bento [UNESP]; Medeiros, Rodrigo Antonio de [UNESP]; Silva, Emily Vivianne Freitas da [UNESP]; Goiato, Marcelo Coelho [UNESP] (Hindawi Publishing Corporation, 2015)
The success of rehabilitation will not depend on just clinical procedures. A proper dental technique (ceramist) is required as well as the respect for some biomimetic principles to obtain the desired final result. This study has the purpose of describing a prosthetic rehabilitation with laminate veneers and all-ceramic crowns of a patient unsatisfied with a previous esthetic treatment because of the negligence of some biomimetic principles. A 45-year-old female patient was admitted to the dental clinic complaining about the lifelike appearance of her all-ceramic restorations. Before the fabrication of new restorations, a mock-up was conducted to verify the patient's satisfaction. A ceramist conducted all the fabrication process so that surface characterizations could be visually verified and the lifelike appearance of natural tooth could be reproduced. After the cementation procedure, the patient reported being satisfied with the lifelike appearance of the new restorations. Based on the clinical findings of the present case report, it can be concluded that the reproduction of the lifelike esthetic appearance of natural teeth and the visualization of the final results before definitive procedures are essential to obtain the clinical success.